Growth and Extended Survival of Escherichia coli O157:H7 in Soil Organic Matter - NandaKafle, Gitanjali; Christie, Amy A.; Vilain, Sébastien; Brözel, Volker S. (Frontiers in Microbiology, 2018)
Enterohaemorrhagic Escherichia coli, such as serotype O157:H7, are a leading cause of food-associated outbreaks. While the primary reservoir is associated with cattle, plant foods have been associated as sources of human infection. E. coli is able to grow in the tissue of food plants such as spinach. While fecal contamination is the primary suspect, soil has been underestimated as a potential reservoir. Persistence of bacterial populations in open systems is the product of growth, death, predation, and competition. Here we report that E. coli O157:H7 can grow using the soluble compounds in soil, and characterize the effect of soil growth in the stationary phase proteome. E. coli 933D (stxII-) was cultured in Soil Extracted Soluble Organic Matter (SESOM) and the culturable count determined for 24 d. The proteomes of exponential and stationary phase populations were characterized by 2D gel electrophoresis and protein spots were identified by MALDI-TOF mass spectrometry. While LB controls displayed a death phase, SESOM grown population remained culturable for 24 d, indicating an altered physiological state with superior longevity. This was not due to decreased cell density on entry to stationary phase as 24h SESOM populations concentrated 10-fold retained their longevity. Principal component analysis showed that stationary phase proteomes from SESOM and LB were different. Differences included proteins involved in stress response, motility, membrane and wall composition, nutrient uptake, translation and protein turnover, and anabolic and catabolic pathways, indicating an altered physiological state of soil-grown cells entering stationary phase. The results suggest that E. coli may be a soil commensal that, in absence of predation and competition, maintains stable populations in soil.